Rare Case of Traumatic Anterior Knee Dislocation of Total Knee Arthroplasty With a Serious Neurovascular Injury - Novotný, Tomáš; Vanaskova, Eliska; Soukup, Jan (Arthroplasty today, 2021)
Traumatic anterior dislocation of a total knee arthroplasty (TKA) is an extremely rare occurrence. There are only a few known cases of this type of dislocation which discuss the high risk of a neurovascular complication. This article describes a traumatic anterior dislocation of the TKA with a severe vascular lesion in a 75-year-old severely comorbid patient. Further complications led to the development of a compartment syndrome. Despite the repeated effort in performing a well-functioning anastomosis of the popliteal artery tear by the vascular surgeon, reperfusion of the lower extremity was not effective. Furthermore, multiorgan system failure due to the reperfusion syndrome evolved. This led to an above-knee amputation as a lifesaving procedure. Despite thorough intensive care therapy, the patient did not survive this complication. Presently there are no reported cases with such severe complications after the luxation of a previously well-functioning TKA leading to the death of the patient.